(untitled) (Research, Society and Development, 2023)
In recent years, the number of studies on child development has grown, at this stage, the main links are provided by the family. A study was carried out with the aim of profiling opportunities in the domestic environment capable of helping to promote children’s motor development. This is a quantitative, descriptive and cross-sectional study, through the application of an adapted instrument called “Affordances in the Home Environment for Motor Development - Baby Scale (AHMD-IS)”, were calculated for a given study variable: Characteristics of the Family, Characteristics of the child, Physical space, Variety of stimulation, Gross mo,tor toys, Fine motor toys and the general AHEM-IS score, these were transferred and tabulated to an Excel 2016 table and treated in the Bioestat software version 5.0. In the profile of family members, it was noticed that 49 (89.9%) had a home of this type, in most of the homes, up to two adults live, 29 (52.7%) and up to two children in 21 (38.1%). Most 38 (69.0%) have lived in the area for more than 12 months and have completed high school23 (41.8%). Regarding children, the majority 29 (52.8%) are male. 54 (98.1%) never attended day care centers or schools, 54 (98.2%) were born weighing 2,500g or more, and 32 (58.19%) considered normal gestational age. It is concluded that the low scores presented by the families reveal the extreme need to search for improvements in the family environment so that there is no damage to the child’s development and the child receives the environmental and family stimulus necessary for his development.